Sustainable social supply chain practices and firm social performance: Framework and empirical evidence - Fernando, Yudi; Halili, Munira; Tseng, Ming-Lang; Tseng, Jiun Wei; Lim, Ming K. (Elsevier Publisher, 2022)
Concerns about social sustainability issues such as child labour, inequality, excessive overtime, and abusive working and living conditions in developing countries' manufacturing sectors have prompted an urgent study on sustainable social supply chain practices. The social pillar of sustainability has then been unnoticed, favouring the more regularly discussed environmental and economic dimensions. This study aims to expand the social sustainability framework to investigate the impact of sustainable social supply chain practices on firm social performance. The electronic survey was conducted on firms that adopted sustainable social practices. The 144 data sets were received from manufacturing firms. The data were analysed using structural equation modelling with PLS-SEM to examine domains and outcomes of sustainable supply chain practices. The result found that social supply chain practices impact the firm's social performance. However, the results indicate that the social element of sustainable procurement does not affect the firm social performance. The results show social fairness challenged manufacturing firms to comply with sustainable production and distribution. Most manufacturing firms are still not aware of their role and social responsibility to develop the local suppliers and community. Sustainability framework has proposed to raise awareness of sustainable practices that drive firms to implement sustainable social supply chain practices and leverage social performance. By being socially responsible, firms can gain improved brand awareness, a favourable corporate reputation, increased sales, observed firm growth and enhanced customer loyalty.